2020
DOI: 10.1038/s43018-020-0053-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals compromised immune microenvironment in precursor stages of multiple myeloma

Abstract: Precursor states of Multiple Myeloma (MM) and its native tumor microenvironment need in-depth molecular characterization to better stratify and treat patients at risk. Using single-cell RNA sequencing of bone marrow cells from precursor stages, MGUS and smoldering myeloma (SMM), to full-blown MM alongside healthy donors, we demonstrate early immune changes during patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
198
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(240 citation statements)
references
References 63 publications
18
198
0
Order By: Relevance
“…However, the risk of infection decreased with the response to therapy, which suggests some immune reconstitution accompanies a lower burden of myeloma. In addition to progressive impairment of humoral immunity, changes across many cell types of the bone marrow immune microenvironment, including Natural Killer (NK), Dendritic, and T-cells, have been observed from MGUS, to SMM, and MM [69]. These observations support the concept that there is progressive immunoparesis that accompanies disease progression from MGUS to MM.…”
Section: Immunodeficiency In Mgusmentioning
confidence: 71%
“…However, the risk of infection decreased with the response to therapy, which suggests some immune reconstitution accompanies a lower burden of myeloma. In addition to progressive impairment of humoral immunity, changes across many cell types of the bone marrow immune microenvironment, including Natural Killer (NK), Dendritic, and T-cells, have been observed from MGUS, to SMM, and MM [69]. These observations support the concept that there is progressive immunoparesis that accompanies disease progression from MGUS to MM.…”
Section: Immunodeficiency In Mgusmentioning
confidence: 71%
“…Using single-cell RNA sequencing of bone marrow cells from the precursor stages of monoclonal gammopathy of unknown significance and smoldering multiple myeloma (SMM), to full-blown MM alongside healthy donors, Zavidij and colleagues [7] confirmed previous concepts about immune changes during patient progression [8], and provided unprecedented resolution about the immune microenvironment in precursor and malignant stages of MM. Interestingly, the same group of authors reported recently that most genetic alterations present in MM patients have already occurred by the time of SMM diagnosis, some of which predict risk of progression [9].…”
Section: Highlighted By Bruno Paivamentioning
confidence: 89%
“…In this study we show that IL-32 is expressed by a fraction of MM cells and that it promotes survival and proliferation of these cells. IL-32 is also expressed by regulatory or senescent/exhausted T cells in MM, but if/how this affects the function of the T-cells is not known 50, 51 . IL-32 is secreted from the MM cells and IL-32 in the BM microenvironment enhance osteoclast differentiation 15 , it can promote IL-6 production from stromal cells 52 and may generate immunosuppressive macrophages, 53 all factors that may lead to a more aggressive disease development.…”
Section: Discussionmentioning
confidence: 99%